2013
DOI: 10.3109/14756366.2013.787422
|View full text |Cite
|
Sign up to set email alerts
|

Sulfa and trimethoprim-like drugs – antimetabolites acting as carbonic anhydrase, dihydropteroate synthase and dihydrofolate reductase inhibitors

Abstract: Recent advances in microbial genomics, synthetic organic chemistry and X-ray crystallography provided opportunities to identify novel antibacterial targets for the development of new classes of antibiotics and to design more potent antimicrobial compounds derived from existing antibiotics in clinical use for decades. The antimetabolites, sulfa drugs and trimethoprim (TMP)-like agents, are inhibitors of three families of enzymes. One family belongs to the carbonic anhydrases, which catalyze a simple but physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
175
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 267 publications
(178 citation statements)
references
References 63 publications
3
175
0
Order By: Relevance
“…26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type. [55][56][57][58]60 Many such enzymes also possess biotechnologic applications for biomimetic CO 2 capture processes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type. [55][56][57][58]60 Many such enzymes also possess biotechnologic applications for biomimetic CO 2 capture processes.…”
mentioning
confidence: 99%
“…4,5,[30][31][32][33][34][35][36][37][38] These enzymes are involved in a multitude of physiologic processes in organisms all over the phylogenetic tree, with six genetically distinct CA classes known to date: the a-, b-, c-, d-, f-and g-CAs. 26,[39][40][41][42][43][44][45][46][47][48][49][50] Their biochemical features are known in detail for at least four classes, together with their distribution and role in various organisms. 32,33,41,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Inhibition and activation studies of many such enzymes from vertebrates, protozoa, fungi and bacteria have shown that they are drug targets for obtaining pharmacological agents of the diuretic, antiglaucoma, antiobesity, antiepileptic, anticancer or anti-infective type.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Only hCA VB and especially hCA II, one of the best catalysts known in nature, show a better activity than HpbCA [38][39][40][41] . Also, it may be observed that the activity of all these enzymes is inhibited by the CA inhibitor (CAI) par excellence, the sulfonamide drug, acetazolamide AAZ [53][54][55][56][57] , which may explain why Ulcosilvanil showed a range of severe side effects, due to inhibition of CA isoforms in other organs than the stomach, or better to say, due to hCAs and not Hpa/bCA inhibition (Table 3).…”
Section: Treatment Of Gastric and Duodenal Ulcers By Ca Inhibitorsmentioning
confidence: 99%
“…They also help tumour growth by supplying HCO À 3 to be used as substrate for cell growth as this anion is required in the synthesis of pyrimidine nucleotides such as cytosine, thymine, and uracil 56 . Thus, specifically targeting the tumour-related isozymes (hCA IX and XII) over the main off target isoenzymes hCA I, and II may be a new antitumor approach, with a sulphonamide CA inhibitor in Phase I clinical trials for the treatment of hypoxic tumors [57][58][59] . However, CA II is also a drug target for antiglaucoma agents, diuretics and highaltitude sickness among others [60][61][62] .…”
Section: +mentioning
confidence: 99%